Searching for a Quantum Critical Point in Rh doped ferromagnetic Ce2. 15Pd1. 95In0.9 - Sereni, J.G.; Giovannini, M.; Gómez Berisso, M.; Saccone, A.; Sereni, Julián (IOP Publishing, 2012)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina